Implementasi Simple Additive Weighting Dalam Menentukan Biji Kopi Terbaik - Muhammad Fichri; Akbar Ramadhan; Farhan Arsyad; Yuwan Jumaryadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
There are several types of coffee in Indonesia. Among the many types of coffee beans, one will find it difficult to choose the best coffee beans among the many types of coffee available. To make it easier for entrepreneurs and coffee connoisseurs to identify coffee beans, a decision support system is needed that can help determine the best coffee based on the given criteria. There are 4 criteria to determine the best coffee beans, namely price, quantity, taste and variety. These criteria are used in developing the system using the simple additive weighting method. Based on the calculation criteria, Sipetung coffee beans are the best coffee beans. Meanwhile, Gayo coffee beans are the last ranked coffee beans based on calculations that have been made.